Unusual Case of Anaplastic Large Cell Lymphoma Presenting as a Breast Mass in a Patient with no History of Breast Implants - Yana Ivashkevich; Yaroslav Chernov; Denis Chinenov; Evgeniy Shpot; Alexander A. Bessonov; Arthy Yoga; Kirill A. Lyapichev; Sergej Konoplev (Case Reports in Pathology)
Adenocarcinoma is the most common malignant neoplasm involving breast tissue. In contrast to carcinomas, the other types of malignant neoplasms involving the breast are relatively uncommon. One of the examples of this rare entity is lymphoma. Traditionally, non-Hodgkin lymphomas (NHL) involving the breast are divided into primary lymphoma of the breast and systemic lymphoma, although the distinction could be challenging. Most of NHL involving breast tissue have B cell origin; T cell NHL represents less than 20% of all lymphoma cases. Anaplastic large cell lymphomas (ALCL) involving the breast accounts for even lower percentage of cases. Similar to ALCL involving other sites, there are several main types of ALCL identified: primary cutaneous ALCL and systemic ALCL, which is subdivided into ALK positive and ALK negative subtypes. Relatively recently, an additional distinct subtype of ALK-negative ALCL was described, which is associated with textured breast implants and needs to be considered as a differential diagnosis if patient has a history of breast implants. Here, we report a case of ALCL presented as a breast mass without history of breast implant and discuss similar cases published in the literature.